PLAN DE MARKETING PARA LA SASTRERIA TRAJES IMPERIAL DE LA CIUDAD DE LOJA - Morocho Collaguazo, Jimmy Stalin (2017)
The present work was developed with the purpose of implementing a Marketing Plan in the company Costumes Imperial of the city of Loja and its way of operating in the market. A situational diagnosis was made to promote and increase its sales volume using As a marketing plan tool. In this research, the problem lies in the Tailoring Imperial Costumes, in addition the objectives of the research are presented, it establishes the information that concerns the reference and historical antecedents, with the theoretical base that studies the research variables. Likewise, the research methodology is presented, showing that the type of research is descriptive, qualitative. It also establishes the techniques, instruments and research, which in this case is the survey aimed at the employees and clients of the tailoring leaving the size of the sample established that will allow to obtain the respective results. As for the Analysis and interpretation of Results, the results obtained in two types of surveys are detailed through tables, figures and analyzes, in this way the interpretative reading, analysis, results and the hypotheses were verified. In the proposal, the topic is developed: Implementation of a marketing plan for the Tailoring Imperial Costumes, as a tool to increase sales volume, which specifies the objectives, location, strategic plan to be developed, the diagnosis of Porter And SWOT until the cost of the plan is presented. In the internal analysis, the EFI Matrix was used, with a weighted value of 3.41, which means that it is stronger than weak, but having the almost average value it can be said that it does not have a stable internal consistency to compete successfully with its Rivals. Finally, we proceed to make the cross-factors in the matrix of high impact SWOT where four strategic objectives are established to implement the marketing plan. The total cost of the Marketing Plan for the year 2018 is $ 1400.00 dollars; For the year 2019 is $ 1025.00 dollars, and for the year 2020 is $ 1025.00 dollars, giving a total of $ 3450.00 dollars